Computer Vision Syndrome - Dotulong, Dean; Rares, Laya M.; Najoan, Imelda H. M. (Universitas Sam Ratulangi, 2021)
Abstract: Computer vision syndrome (CVS) describes a group of eye and vision related problems that result from prolonged computer use or other gadgets. Its clinical manifestations maybe are not very disturbing for most people. Therefore, it tends to cause delayed treatment. If CVS is not well treated, there would be obstacles in daily life such as decreased productivity, increased failure in working or studying, and also low job satisfaction. This study was aimed to obtain a general view of CVS that involved the development of CVS, subjective complaints, and the its risk factors. This was a literature review study using three databases, as follows: Pubmed, ClinicalKey, and Google Scholar. The keywords were